Heorot and the Plundered Hoard: A Study of Beowulf - Helder, Willem (My University, 1974)
During the age in which Beowulf was written, Christianity was the prevailing cultural force. Since early medieval religion was rooted in biblical typology, the principles of which were widely disseminated by the liturgy of the Church, we may assume that the resulting Weltanschauung also influenced Old English literature. While it is increasingly being recognized that the poetry of the Anglo-Saxons is the product of the typological imagination, Beowulf is usually regarded as somewhat of an exception. Until now, no typological study of the poem as a whole has appeared. In order to interpret its major symbols and illuminate its perennial cruces, Beowulf needs to be studied in its literary context. An understanding of the poem is therefore promoted by a consideration of its relationship to the literature of the typology-based tradition: other Old English poetry (which is mostly biblical or hagiographic in theme), the liturgical texts (in which the Scriptures, especially the Psalms, are the prominent sources), as well as the exegetical and homiletical writings of the Church Fathers and their medieval successors. The soundness of taking such material into account in the study of Beowulf is demonstrated by the fact that this method yields not only explanations of many individual elements but also a unified interpretation of the poem in its entirety. The meaning of Heorot, the goldhall, can thus be determined by comparing it to structures that are discussed in similar terms in the literature known to the Anglo-Saxons --for example, the temple or the newly created earth when it is described as a building. As a result it can be shown that, contrary to what some have argued, neither the perfect beginning of the hall nor the misery subsequently caused by the monster Grendel is evidence of the sinful pride of Hrothgar, its builder. Heorot's typological --and, hence, also baptismal --connotations lead us to the conclusion that Hrothgar's seemingly reprehensible inertia in the face of Grendel's attacks is entirely appropriate in one who, like the mournful ones in the Old English Advent, can only await deliverance. Adiscussion of the spring motifs in the poem helps to identify Beowulf as the heroic redeemer which the situation calls for. Numerous other details, when examined in a typological perspective, help to confirm this identity. Furthermore, Beowulf can be defended against those who cast aspersions on his desire to defeat the dragon and win its gold for his people. The role of the thief provides important clues to the meaning of Beowulf's own spoiling of the dragon's hoard. It can be shown that Christ's rifling of the devil's hoard constitutes the paradigm. Like Beowulf's cleansing of Heorot, the plundering is a redemptive activity. Moreover, since the poet presents it as a doomsday motif, it forms an extension of the Flood and baptism typology to which he repeatedly alludes in the earlier presentation of Beowulf's fights with the Grendel kin. Time and again the Beowulf poet's choice of words and details reveals that he practised his craft within a tradition in which his creativeness was bound and disciplined by the objectiveness of a particular structure of images. We perceive in all the rich variety of his work the unifying effect of the typological imagination. It is in the typological mode of Beowulf that the key to its meaning and artistry is to be found.
Keywords: Beowulf, cultural force, Old English literature, typological, context, biblical, liturgical texts